Correction: Enzyme-responsive reporter molecules for selective localization and fluorescence imaging of pathogenic biofilms. Issue 75 (11th September 2017) - Aw, Junxin; Widjaja, Frances; Ding, Yichen; Mu, Jing; Yang, Liang; Xing, Bengang
Abstract : Correction for 'Enzyme-responsive reporter molecules for selective localization and fluorescence imaging of pathogenic biofilms' by Junxin Aw et al., Chem. Commun., 2017, 53, 3330–3333.